TINJAUAN VO2MAX PADA ATLET TINJU PUTERA DAN PUTERI CLUB DENPAL BOXING CAMP PEKANBARU - Risnawati julita; Saripin '; Kristi agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: All boxing athlete must have good durability because boxing is a sport game conducted amateur consisting of 3x3 minutes to son and 4x2 minutes to daughter with 1 minute rest, so as to be able to survive in a good game in need endurance physical specimen. The purpose of this study was to determine the ability of VO2max How Athletes Boxing Putera and Puteri club denpal pekanbaru boxing camp. VO2 Max is a measure kapisitas each individual in generating the energy required in endurance activities without experiencing excessive fatigue. This research is non-experimental quantitative study using a model of quantitative descriptive approach. Sampling technique that is the entire population of athletes boxing club denpal son and daughter of boxing camp pekanbaru, the sample in this study is the son and daughter of boxing athlete boxing club denpal pekanbaru camp amounted to 6 people. Therefore, to determine the durability of the player can be known based on the level of VO2 Max through tests Multistage Fitness Test (MFT). The research results are the average - average level of VO2max male athlete boxing club boxing camp denpal pekanbaru 34.87 ml / kg / min and the average - average level boxing athlete's VO2max daughter denpal club boxing camp pekanbaru 24.65 ml / kg / min. It can be concluded that the average level of the athlete's VO2max son and daughter of a boxing club boxing camp denpal pekanbaru included in the low category. Keywords: Boxing, VO2max, Club Denpal Boxing Camp Pekanbaru